2016
DOI: 10.1002/adhm.201600804
|View full text |Cite
|
Sign up to set email alerts
|

Improved Anticancer Photothermal Therapy Using the Bystander Effect Enhanced by Antiarrhythmic Peptide Conjugated Dopamine‐Modified Reduced Graphene Oxide Nanocomposite

Abstract: Despite tremendous efforts toward developing novel near-infrared (NIR)-absorbing nanomaterials, improvement in therapeutic efficiency remains a formidable challenge in photothermal cancer therapy. This study aims to synthesize a specific peptide conjugated polydopamine-modified reduced graphene oxide (pDA/rGO) nanocomposite that promotes the bystander effect to facilitate cancer treatment using NIR-activated photothermal therapy. To prepare a nanoplatform capable of promoting the bystander effect in cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 47 publications
0
41
1
Order By: Relevance
“…It has been reported that hyperthermia to ∼57°C can result in irreversible tumor cell damage and the best PTT effect (Figure 3d). 31,32 This declaration was proven by the histopathological tissue analysis following hematoxylin and eosin (H&E) staining of tumor sections from mice after the treatments. As shown in Figure 3e, compared with CuS@mSiO 2 -DOX, CuS@mSiO 2 -DOX/i-motif/TK-mPEG resulted in more necrotic areas in tumor tissues, indicating more severe tumor damage by both enhanced PTT and chemotherapy.…”
Section: In Vivo Tumor Accumulation Of the Dual-modified Nanoparticlementioning
confidence: 99%
“…It has been reported that hyperthermia to ∼57°C can result in irreversible tumor cell damage and the best PTT effect (Figure 3d). 31,32 This declaration was proven by the histopathological tissue analysis following hematoxylin and eosin (H&E) staining of tumor sections from mice after the treatments. As shown in Figure 3e, compared with CuS@mSiO 2 -DOX, CuS@mSiO 2 -DOX/i-motif/TK-mPEG resulted in more necrotic areas in tumor tissues, indicating more severe tumor damage by both enhanced PTT and chemotherapy.…”
Section: In Vivo Tumor Accumulation Of the Dual-modified Nanoparticlementioning
confidence: 99%
“…To confer specificity to nanostructures, one may conjugate antibodies that target specific bacterial strains (26), following upon extensive work targeting nanoparticles for cancer cell treatment (27)(28)(29)(30). However, phage-based strategies possess several advantages compared to antibody-based strategies.…”
Section: Significancementioning
confidence: 99%
“…20,21 Since the seminal report on use of graphene oxide (GO), a derivative of graphene, this compound has seen increasing application in biomedical areas, including cell proliferation and differentiation, drug delivery, immune response, and anticancer therapy. 15,18,20,[22][23][24] Significantly, GO has abundant oxygen functional groups, including hydroxyl, epoxy, carbonyl, and carboxyl groups. 25 The effect of GO can be modulated by modification of its oxygen moieties as well as altering chemical functionality on graphene layers.…”
Section: Introductionmentioning
confidence: 99%